Disaster Management in Earthquake-Prone Countries: Lessons from the Public Administration Systems of Japan and the Philippines - Wahyudi Mokobombang (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This comprehensive study examines the disaster management strategies of Japan and the Philippines, focusing on their responses to earthquakes through the lens of Systems Theory. Japan's centralised model emphasises hierarchical coordination, advanced technological integration, and pre-disaster planning, ensuring rapid and efficient responses. Conversely, the Philippines employs a decentralised framework, leveraging community-based initiatives and localised decision-making, though often constrained by resource disparities. Through rigorous data collection, including field observations, stakeholder interviews, and policy analysis, this research provides a comparative analysis highlighting both systems' strengths and limitations. The findings reveal that Japan's technological infrastructure and institutional coordination excel in early warning and response efficiency, while the Philippines' grassroots participation fosters community resilience despite resource constraints. This study proposes a hybrid approach that integrates centralised coordination with community-driven participation to enhance disaster resilience in earthquake-prone nations, offering transferable lessons for public administration systems worldwide.